Land drainage and flood defence delegate information : Monday 1 December 1997 : a joint initiative of Thomas Telford Conferences and the Boards of the Institution of Civil Engineers. (Thomas Telford series of the Institution of Civil Engineers' seminars., 1997)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in December 1997.